Radiative pulsed L-mode operation in ARC-class reactors. (1st December 2022) - Frank, S.J.; Perks, C.J.; Nelson, A.O.; Qian, T.; Jin, S.; Cavallaro, A.; Rutkowski, A.; Reiman, A.; Freidberg, J.P.; Rodriguez-Fernandez, P.; Whyte, D.
Abstract: A new ARC-class, highly-radiative, pulsed, L-mode, burning plasma scenario is developed and evaluated as a candidate for future tokamak reactors. Pulsed inductive operation alleviates the stringent current drive requirements of steady-state reactors, and operation in L-mode affords ELM-free access to ∼ 90 % core radiation fractions, significantly reducing the divertor power handling requirements. In this configuration the fusion power density can be maximized despite L-mode confinement by utilizing high-field to increase plasma densities and current. This allows us to obtain high gain in robust scenarios in compact devices with P fus > 1000 MW despite low confinement. We demonstrate the feasibility of such scenarios here; first by showing that they avoid violating 0D tokamak limits, and then by performing self-consistent integrated simulations of flattop operation including neoclassical and turbulent transport, magnetic equilibrium, and radiofrequency current drive models. Finally we examine the potential effect of introducing negative triangularity with a 0D model. Our results show high-field radiative pulsed L-mode scenarios are a promising alternative to the typical steady state advanced tokamak scenarios which have dominated tokamak reactor development.